Occurrence of Quinolone-Resistance Genes in Ciprofloxacin-Resistant Salmonella Enterica Serotype Typhi Isolated form Blood Sample of Patients with Typhoid Fever - S. Hassan, Jabbar; Al-Tamimi, Bushra J.; Ghazi Hassan, Fuad (Iraqi Journal of Pharmaceutical Sciences, 2022)
Salmonella is approved as a common foodborne pathogen, causing major health problems throughout the world particularly in low‐ and middle‐income countries. Low-level fluoroquinolone resistance is conferred by both chromosomal and plasmid-encoded resistance, this research was carried out look into the occurrence rate of qnrA,qnrB and qnrS genes  in  Salmonella enterica serotype Typhi Cipr  ofloxacin-resistant insulate from blood samples of patients with typhoid fever. Fifteen Salmonella enterica serotype Typhi isolated previously from patients with typhoid fever were included in this study. All bacterial isolates were confirmed to have ciprofloxacin resistant by VITEK 2 microbial identification system; after plasmid DNA extraction; multiplex-PCR was done with primer sequences intended to plasmid-mediated quinolone-resistance genes which is qnrA, qnrB, and qnrS. In this study; it was 21 qur genes amongst 15 isolates. The qnrS gene was the commonest (10/21, 47.6%) followed by qnrA (6/21, 28.5%), whereas only 4 isolates were positive for qnrB (5/21, 23.8%). Some isolates had more than one qnr genes. So, Ciprofloxacin-resistant Salmonella typhi can have more than one gene at the same time; and the most occurrence rate in regards to qnr gene in this study was qnrS compared to qnrA and qnrB